Post-colonial theory and English literature : a reader (Edinburgh : Edinburgh University Press, 1999)
Includes critical essays on William Shakespeare's The Tempest; Daniel Defoe's Robinson Crusoe; Charlotte Bronte's Jane Eyre; Joseph Conrad's Heart of Darkness; Rudyard Kipling's Kim; James Joyce's Ulysses; E.M. Forster's A passage to India; and, Salman Rushdie's The satanic verses.
The tempest / William Shakespeare -- Robinson Crusoe / Daniel Defoe -- Jane Eyre / Charlotte Brontë -- Heart of darkness / Joseph Conrad -- Kim / Rudyard Kipling -- Ulysses / James Joyce -- A passage to India / E.M. Forster -- The satanic verses / Salman Rushdie.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: English fiction -- History and criticism; Postcolonialism; Colonies in literature; Imperialism in literature; Roman anglais -- Histoire et critique; Postcolonialisme; Colonies dans la littérature.; Impérialisme dans la littérature.; postcolonialism; 18.05 English literature; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- General; Colonies in literature; English fiction; Imperialism in literature; Postcolonialism; Aufsatzsammlung; Kolonialismus; Literatur; Literaturtheorie; Postkoloniale Literatur; Fictie; Postkolonialisme; Kolonialisme; Imperialisme; Englisch; Geschichte 1611-1988.; English literature -- History and criticism; Imperialism in literature; Criticism, interpretation, etc; Anthologies (form)